Takhrij and Syarah Hadith of Chemistry: Study of the Benefits of Hot Iron (Kay) in terms of Health - Azmi Fathul Rohman; Siti Rahmah; Muhamad Dede Rodliyana; Ayi Rahman; Gina Giftia Azmiana Delilah (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about the benefits of hot iron (Kay) in terms of health. This research method is qualitative through the takhrij and syarah hadith approaches with chemical analysis. The results and discussion of this study indicate that kay is a treatment or therapy by attaching hot iron to the wound area or to acupuncture points on the human body by considering the anatomy of the human body. This study concludes that using the kay treatment method is recommended to be the last treatment (there is no other treatment option), because the pain caused can trigger other diseases to enter the body, while the law of kay treatment varies depending on the situation and condition of the patient. itself so that the law can be permissible, makruh and even haram (prohibited).